Increased exhaled nitric oxide in patients with stable chronic obstructive pulmonary disease. Issue 7 (1st July 1999) - Corradi, Massimo; Majori, Maria; Cacciani, Gian Carlo; Consigli, Gian Franco; de'Munari, Eriberto; Pesci, Alberto
Abstract : BACKGROUND: Nitric oxide (NO) plays an important role as an inflammatory mediator in the airways. Since chronic obstructive pulmonary disease (COPD) is characterised by airway inflammation, a study was undertaken to determine NO levels in the exhaled air of patients with COPD. METHODS: Two groups of patients with clinically stable COPD were studied, 10 current smokers and 10 ex-smokers. Two control groups of healthy subjects consisting of 10 current smokers and 20 non-smokers were also studied. Exhaled NO levels were measured by the collection bag technique and NO chemiluminescence analyser. RESULTS: Mean (SE) levels of exhaled NO in ex-smokers and current smokers with COPD (25.7 (3.0) ppb and 10.2 (1.4) ppb, respectively) were significantly higher than in non-smoker and current smoker control subjects (9.4 (0.8) ppb and 4.6 (0.4) ppb, respectively). In current smokers with COPD exhaled levels of NO were significantly lower than in ex-smokers. In this latter group of patients there was a significant negative correlation between smoking history (pack years) and levels of exhaled NO ( r = –0.8, p = 0.002). A positive correlation was seen between forced expiratory volume in one second (FEV1 ) and levels of exhaled NO ( r = 0.65, p = 0.001) in patients with COPD. CONCLUSIONS: These data show that exhaled NO is increased in patients with stable COPD, both current and ex-smokers, compared with healthy control subjects.